Hierarchical porous carbons by liquid phase impregnation of zeolite templates with lignin solution - Valero-Romero, María José; Márquez-Franco, Eva María; Bedia García-Matamoros, Jorge; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (ELSEVIER, 2014)
Templated carbon materials (TCs) with hierarchical pore structure were obtained by liquid phase impreg- nation of different zeolite templates using Alcell lignin solutions as carbon precursor. The effect of synthesis conditions such as templating mixture (lignin/zeolite), carbonization temperature (500, 700 and 900 °C) and of zeolite framework on the structural and chemical properties of the resultant carbons was analyzed. The main original aspect of this work is the use of Alcell lignin as carbon precursor, a low- cost co-product derived from the papermaking industry, to obtain porous carbon materials with different pore size distribution, depending on the inorganic template used. Microporosity is developed from both the replication of the hard template and the carbonization of lignin, whereas mesoporosity can be adjusted by and adequate selection of the hard template and infiltration conditions. The TCs present interesting surface chemistry features, with a relatively high amount of nitrogen and oxygen stable sur- face groups, such as pyrrolic and pyridinic and hydroxyl and carbonyl type, respectively, which seem to have been transferred from the surface ammonia ions and oxygen of the zeolite template to the carbon materials during the synthesis. The hydroxyl groups seem to be responsible of the relatively high Brönsted acidity of the TCs.
Keywords: Zeolitas; Templated carbons; Nanocasting; Alcell lignin; Zeolites; Hierarchical porous carbon